Corruption, judicial accountability and inequality: Unfair procedures may benefit the worst-off - Niclas Berggren; Christian Bjørnskov (Research Institute of Industrial Economics (IFN), 2019)
We ask whether, as many seem to think, corruption worsens, and judicial accountability improves, inequality, and investigate this empirically using data from 145 countries 1960.2014. We relate perceived corruption and de facto judicial accountability to gross-income inequality and consumption inequality. The study shows that corruption is negatively, and that judicial accountability is positively, related to both types of inequality. The estimates are particularly pronounced in democracies and arguably causal, as we find that the full effect only occurs after institutional stability has been established; The findings suggest that "unfair procedures" - corruption and deviations from judicial accountability - may benefit the economically worst off and worsen the situation of the economic elite.
Keywords: C31; D02; D31; D72; D73; E26; 330; Corruption; Inequality; Institutions; Accountability; Rent-seeking